2005
DOI: 10.1152/ajprenal.00038.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of fibrate protects from cisplatin-induced ARF

Abstract: Recently, we demonstrated that peroxisome proliferator-activated receptor-alpha (PPARalpha) ligand ameliorates cisplatin-induced acute renal failure (ARF) by preventing inhibition of substrate oxidation, and also by preventing apoptosis and necrosis of the proximal tubule (Li S, Bhatt R, Megyesi J, Gokden N, Shah SV, and Portilla D. Am J Physiol Renal Physiol 287: F990-F998, 2004). In the following studies, we examined the protective effect of PPARalpha ligand on cisplatin-induced inflammatory responses during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 41 publications
12
87
1
Order By: Relevance
“…Both the Jun Nterminal kinase (Francescato et al 2007) and peroxisome proliferator-activated receptor (Li et al 2005;Lee et al 2006) pathways have been shown to mediate the production of inflammatory cytokines; interestingly, inhibition of these pathways is protective against cisplatin-induced nephrotoxicity (Lee et al 2006;Francescato et al 2007). We hypothesize that the anti-inflammatory effects of sEH inhibition are responsible for the protection against cisplatin-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 88%
“…Both the Jun Nterminal kinase (Francescato et al 2007) and peroxisome proliferator-activated receptor (Li et al 2005;Lee et al 2006) pathways have been shown to mediate the production of inflammatory cytokines; interestingly, inhibition of these pathways is protective against cisplatin-induced nephrotoxicity (Lee et al 2006;Francescato et al 2007). We hypothesize that the anti-inflammatory effects of sEH inhibition are responsible for the protection against cisplatin-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 88%
“…However, the currently available data are somewhat conflicting as to the precise role of cisplatin in regulating NF-κB activation and DNA binding. (24,25,34,36,37) Our data also suggested that the response of NF-κB to distinct cancer therapies might also vary, depending on the cell type and context, since numerous evidences showed that NF-κB act as a antiapoptotic factor and tumor promotor, while under some circumstances NF-kB can contribute to genotoxic stress-induced apoptosis. (38) Intercellular adhesion molecule-1 (ICAM-1, CD54) is a member of the immunoglobulin superfamily.…”
Section: Discussionmentioning
confidence: 74%
“…Approaches to reduce the incidence and severity of cisplatin-associated toxicity are under intensive investigation indicate that. (9,12,18,24) Cisplatininduced nephrotoxicity, ototoxicity, and neurotoxicity have been associated with potential microvascular damage, (17)(18)(19) and previous animal experiments and clinical reports have demonstrated that vascular factors (20)(21)(22) contribute to renal dysfunction following exposure to cisplatin. The mechanisms underlying these troublesome vascular-injury-associated side-effects, which are regarded as crucial in the pathogenesis of tissue damage, might involve the proliferation inhibition effect of cisplatin on endothelial cells in vitro (18,32,33) and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also incapable of responding to fasting states, resulting in hypoacetonemia, which is associated with severe hypothermia and hypoglycemia (7). PPARα is associated with the inflammatory process as knockout mice show a prolonged inflammatory response (9)(10)(11). Furthermore, these mice present alterations in their cardiac function (12).…”
Section: Metabolism and Ppar Agonistsmentioning
confidence: 99%